Kontaktverbindungen für aussteifende Scheiben aus Brettsperrholz - Schmidt, Tobias (KIT Scientific Publishing, 2018)
Cross-laminated timber (CLT) is already being used successfully in residential, commercial and industrial buildings for different reasons. High in-plane shear strength and stiffness of the CLT itself make CLT members especially suited for bracing elements with in-plane loads. To better use the potential of CLT under static in-plane loading, so called contact joints were developed with increased stiffness and load-carrying capacities using CNC automatic processing machines.
German
Keywords: Erdbeben; Kontaktverbindung; diaphragms; Brettsperrholz; cross-laminated-timber; Aussteifung; contact-joint; earthquake; Scheiben